Complejo nuestra señora del Rosario (2020)
The Nuestra Señora del Rosario Complex seeks to rehabilitate the built heritage and morphology of the Las Cruces neighborhood, revitalizing the old group of buildings that made up the Nuestra Señora del Rosario School, turning it into a cultural and commercial development project, and thus enhancing the connection of the Crossings with the historic center of Bogotá (CHB), through the recovery of forgotten spaces with high historical value, through the change of uses, adapting to the needs of the population and the city.